2016
DOI: 10.3390/ijms17111937
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin E Analog Gamma-Tocotrienol (GT3) and Statins Synergistically Up-Regulate Endothelial Thrombomodulin (TM)

Abstract: Statins; a class of routinely prescribed cholesterol-lowering drugs; inhibit 3-hydroxy-3-methylglutaryl-coenzymeA reductase (HMGCR) and strongly induce endothelial thrombomodulin (TM); which is known to have anti-inflammatory; anti-coagulation; anti-oxidant; and radioprotective properties. However; high-dose toxicity limits the clinical use of statins. The vitamin E family member gamma-tocotrienol (GT3) also suppresses HMGCR activity and induces TM expression without causing significant adverse side effects; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(51 reference statements)
0
7
1
Order By: Relevance
“…The pleiotropic endothelium-modifying properties of TM are translated into beneficial effects of recombinant human TM in rodent models of endotoxininduced pulmonary vascular damage, ischemia-reperfusion kidney or liver injury, preeclampsia, STEC-HUS and acute ischemic stroke [30][31][32][33][34][35]. Of note, statins increase the endothelial expression of TM, possibly contributing to its beneficial cardiovascular properties [36], and acti- The thrombin (IIa)-binding region has been localized to the fifth and sixth EGF-like domains, while the fourth EGF-like domain is required for protein C binding to the thrombin-TM complex. The serine/threonine-rich spacer region is the site of glycosaminoglycan (GAG) and especially chondroitin sulphate attachment, enabling the interaction between TM and factor H, which is a cofactor for the factor I-mediated cleavage of C3b into inactive fragments (iC3b).…”
Section: Tm and Endothelial Dysfunctionmentioning
confidence: 99%
“…The pleiotropic endothelium-modifying properties of TM are translated into beneficial effects of recombinant human TM in rodent models of endotoxininduced pulmonary vascular damage, ischemia-reperfusion kidney or liver injury, preeclampsia, STEC-HUS and acute ischemic stroke [30][31][32][33][34][35]. Of note, statins increase the endothelial expression of TM, possibly contributing to its beneficial cardiovascular properties [36], and acti- The thrombin (IIa)-binding region has been localized to the fifth and sixth EGF-like domains, while the fourth EGF-like domain is required for protein C binding to the thrombin-TM complex. The serine/threonine-rich spacer region is the site of glycosaminoglycan (GAG) and especially chondroitin sulphate attachment, enabling the interaction between TM and factor H, which is a cofactor for the factor I-mediated cleavage of C3b into inactive fragments (iC3b).…”
Section: Tm and Endothelial Dysfunctionmentioning
confidence: 99%
“…However, no study has investigated whether GT3, which can also inhibit HMG-CoA reductase by triggering posttranslational degradation of the enzyme, has efficacy similar to that of statins for ERK5 activation in endothelial cells. Notably, we demonstrated that GT3 and statins synergistically upregulate expression of KLF2 and TM and generation of APC in endothelial cells 38 , which are under positive control of ERK5 activation. In addition, GGTi upregulates KLF2 via ERK5 activation 37 .…”
Section: Discussionmentioning
confidence: 79%
“…We tested the efficacy of inhibitors of the mevalonate pathway, specifically, HMG-CoA reductase inhibitors (i.e., atorvastatin and GT3) and GGTi, in attenuating KLF2 suppression after fractionated radiation. We and others have shown HMG-CoA reductase inhibitors enhanced the expression of KLF2 and its downstream target molecules, such as TM and eNOS and provided radiation protection 28,30,38,39,41 . Treatment with atorvastatin, GT3, and GGTi significantly prevented fractionated radiation-induced suppression of not only KLF2 but also its downstream target molecules TM and eNOS (Fig.…”
Section: Mevalonate Pathway Inhibitors Prevent Fractionated Radiationmentioning
confidence: 83%
“…Ionizing radiation negatively affects TM expression (48,49), while activation of the APC pathway and administration of exogenous recombinant TM protect against radiation toxicity (50,51). γ-Tocotrienol induces the expression of TM in primary and immortalized human endothelial cells (45). Moreover, γ-tocotrienol-mediated protection against radiation lethality is dependent on TM, indicating the importance of TM in γ-tocotrienol’s mechanisms of action (52).…”
Section: Tocotrienols Are Potent Radiation Protectorsmentioning
confidence: 99%
“…KLF2 has been associated with endothelial anti-inflammatory, anti-coagulant, antioxidant, anti-adhesive, and anti-permeability properties (58). γ-Tocotrienol and statins synergistically enhance endothelial KLF2 expression as well as the expression and functional activity of TM (45). TM’s transcription can also be positively regulated by the transcription factor, heat shock factor 1 (HSF1).…”
Section: Tocotrienols Are Potent Radiation Protectorsmentioning
confidence: 99%